The Effect of Mindfulness Meditation on Academic Burnout and Perceived Stress among Muslim Students: A Quasi-experimental Approach‏ - Aamer Aldbyani; Mohammed Hasan Ali Al-Abyadh (Islamic Guidance and Counseling Journal, 2023)
Mindfulness occurs in different populations, regardless of their religions, ages, and cultures, but the studies on Muslim backgrounds are insufficient. This study aims to empirically investigate mindfulness's benefits on academic outcomes among Yemeni students. A total of 160 Yemeni students were recruited to complete the Maslach Burnout Inventory (MBI-SS) and the Perceived Stress Scale (PSS) and divided into two groups (experimental group = 80, control group = 80). The experimental group received mindfulness training, while the control group did not receive any training. After the experiment, both groups completed the questionnaires again. The results revealed that the experimental group's emotional exhaustion, cynicism, lack of academic efficacy, and perceived stress were decreased compared to the control group. We concluded that mindfulness meditation training decreased academic burnout and stress among Yemeni students. We suggest mindfulness meditation training could be a good program for decreasing academic problems among Muslim students.